Evaluation of abdominal fat index by ultrasonography and its relationship with psoriasis and metabolic syndrome - Gönül, Müzeyyen; Tatar, İdil; Canpolat, Filiz; Kurmus, Gökçe Işıl; Ergin, Can; Hekimoğlu, Baki (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Accumulating evidence indicates that psoriasis is associated with obesity and metabolic syndrome. Psoriasis and obesity share similar inflammatory mediators, and obesity may potentiate some inflammatory cytokines seen in psoriasis. Body fat distribution, particularly visceral adipose tissue (VAT), is an important factor in metabolic syndrome and atherosclerotic diseases. An association has been demonstrated between psoriasis and abdominal VAT measured by computed tomography (CT). Aim : To measure abdominal VAT noninvasively by ultrasonography (USG) in patients with psoriasis and investigated its relation to psoriasis and metabolic syndrome. Material and methods : The study population consisted of 41 psoriasis patients and 41 control subjects matched for age, sex, and body mass index. The maximal preperitoneal fat thickness (Pmax) at the anterior surface of the liver and the minimal subcutaneous fat thickness (Smin) of the abdomen were measured by USG. The abdominal fat index (AFI = Pmax/Smin ratio) was calculated and the results were compared between groups. Results : The rate of metabolic syndrome was significantly higher in psoriasis patients (p = 0.0018). The mean AFI was similar in both groups. AFI was not associated with psoriasis in subjects with metabolic syndrome (p = 0.495) or with Psoriasis Area and Severity Index (r = 0.123, p = 0.443). Conclusions : This is the first study to evaluate abdominal VAT by USG. Computed tomography may be more reliable than USG, but its high cost and radiation exposure are major disadvantages. Further studies are required to determine the relationships between psoriasis and VAT.